TINGKAT KEPUASAN MAHASISWA TERHADAP KUALITAS PELAYANAN PADA BAGIAN ADMINISTRASI DAN KEUANGAN FAKULTAS EKONOMI UNIVERSITAS LANCANG KUNING PEKANBARU - wita dwika listihana; nurhayani lubis; afvan aquino (Universitas Lancang Kuning, 2017)
Abstract: Student satisfaction on the quality of service on the administration and finance Faculty of Economics, University of Lancang Kuning Pekanbaru (UNILAK) become a concern. Through survey research method and sample of this study amounted to 342 respondents from the number of students of the Faculty of Economics UNILAK calculated from the third semester, V, and VII by using stratified random sampling technique and data analysis in this study is using qualitative descriptive method. Data analysis techniques in this study using Importance-Performance Analysis (IPA). The results obtained from the study that the calculation of CSI values obtained by 0.69 where the value is at the value of CSI 0.66 to 0.80. This means that the value of CSI is included in the criteria of satisfaction to show that students are satisfied with the quality of administrative and financial services Faculty of Economics, University of Lancang Kuning.Keywords: Satisfaction, Quality of Service, IPA, and CSI